PAX7 target genes are globally repressed in facioscapulohumeral muscular dystrophy skeletal muscle - Christopher R. S. Banerji (Nature Portfolio, 2017)
Facioscapulohumeral muscular dystrophy is a myopathy linked to ectopic expression of the DUX4 transcription factor. The authors show that the suppression of targets genes of the myogenesis regulator PAX7 is a signature of FSHD, and might explain oxidative stress sensitivity and epigenetic changes.